1998
DOI: 10.1136/hrt.80.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Troponin T measurement after myocardial infarction can identify left ventricular ejection of less than 40%

Abstract: Aim-To determine whether measurement of serum troponin T concentration after first acute myocardial infarction can be used to identify patients with a left ventricular ejection fraction of < 40%, who have an adverse prognosis. Conclusion-Serum troponin T concentration measured 12-48 hours after admission for first myocardial infarction is a reliable, simple, quick, inexpensive, noninvasive method for identifying patients with a left ventricular ejection fraction of < 40% for whom there is a poor prognosis. (He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 12 publications
0
30
0
1
Order By: Relevance
“…These results indicate that in patients with NSTE ACS, revascularization during index hospitalization attenuates the adverse prognostic importance of in-hospital peak troponin level, potentially at least, in part, by reduction in recurrent MI. Peak troponin levels during MI have been shown to correlate with infarct size and left ventricular ejection fraction, 2 which are major determinants of mortality after MI. 3 Although increased mortality at the highest levels of troponin might be a consequence of myocardial damage large enough to cause decreased left ventricular function, this cannot explain the greater risk of death in patients with only minor elevations of troponin where left ventricular function is preserved.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that in patients with NSTE ACS, revascularization during index hospitalization attenuates the adverse prognostic importance of in-hospital peak troponin level, potentially at least, in part, by reduction in recurrent MI. Peak troponin levels during MI have been shown to correlate with infarct size and left ventricular ejection fraction, 2 which are major determinants of mortality after MI. 3 Although increased mortality at the highest levels of troponin might be a consequence of myocardial damage large enough to cause decreased left ventricular function, this cannot explain the greater risk of death in patients with only minor elevations of troponin where left ventricular function is preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore some patients may develop clinically important myocardial dysfunction due to sublethal injury that does not result in CK-MB release. The major advantage of cTnT over CK-MB is its ability to detect even minimal myocardial cell damage with high sensitivity and specificity that is undetectable by conventional enzyme methods (Mair 1997;Rao et al 1998;Jurlander et al 2000;Lindahl et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The determination and urgent treatment of complications of stroke would prominently decrease morbidity and mortality due to stroke (Rao et al 1998). The mortality during the first days after stroke is generally due to brain damage, whereas in the following weeks deaths are due to stroke complications.…”
Section: )mentioning
confidence: 99%
“…Troponin measurement will also provide quantification of damage [61,62] . It can be shown that cardiac troponin measurements allow prediction of ejection fraction [63][64][65][66] and so quantification of infarct size [67] .…”
Section: Patients Presenting With Stemimentioning
confidence: 99%